Electric power generation, transmission, and distribution - Grigsby, Leonard L. (Electric power engineering series., 2012)
"The generation, delivery and utilization of electric power and energy remains one of the most challenging and exciting fields of electrical engineering. The astounding technological developments of our age are highly dependent upon a safe, reliable and economic supply of electric power. The objective of the Electric Power Engineering Handbook is to provide a contemporary overview of this far-reaching field as well as a useful guide and educational resource for its study. It is intended to define electric power engineering by bringing together the core of knowledge from all of the many topics encompassed by the field. The articles are written primarily for the electric power engineering professional who is seeking factual information and secondarily for the professional from other engineering disciplines who wants an overview of the entire field or specific information on one aspect of it"--